1998
DOI: 10.1046/j.1365-313x.1998.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in Arabidopsis monitored using cDNA arrays

Abstract: SummaryLarge numbers of genes are being discovered on a daily basis for a variety of organisms including Arabidopsis thaliana. To obtain more functional information on these genes, efficient expression monitoring methods need to be developed. In this report we studied the steady-state mRNA levels of over 800 Arabidopsis genes in parallel using high-density arrays of partially sequenced cDNA. The technology is simple and robust and reliably permits the detection of down to twofold variation in mRNA levels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
8

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 25 publications
3
56
0
8
Order By: Relevance
“…Weak expression or low specific activity of cDNA probes (Seki et al 2001) could account for differences reported between macroarray results and RNA gel blots (Taniguchi et al 2001) or QRT-PCR (Desprez et al 1998;Kurth et al 2002).…”
Section: Rna Gel Blot Analysismentioning
confidence: 99%
“…Weak expression or low specific activity of cDNA probes (Seki et al 2001) could account for differences reported between macroarray results and RNA gel blots (Taniguchi et al 2001) or QRT-PCR (Desprez et al 1998;Kurth et al 2002).…”
Section: Rna Gel Blot Analysismentioning
confidence: 99%
“…Filter arrays were produced according to a published protocol [21], with minor modifications. A cDNA library (ZAP Express TM , Stratagene, La Jolla, CA) constructed from ovules ((/3 to 15 DPA) of the wild type G. hirsutum cv.…”
Section: Preparation Of Cdna Filter Arraysmentioning
confidence: 99%
“…The complete sequencing of the Arabidopsis genome (Arabidopsis Genome Initiative [AGI], 2000) and the expansion of functional genomics in this model plant attest to the power of genomic approaches in addressing important questions in plant biology. Large-scale analysis of gene expression in Arabidopsis using cDNA and oligonucleotide arrays has given new insights into photosynthesis (Desprez et al, 1998), biotic and abiotic stresses (Maleck et al, 2000;Schenk et al, 2000;Bohnert et al, 2001;Seki et al, 2001), nitrogen assimilation (Wang et al, 2000), and organ development (Ruan et al, 1998;Girke et al, 2000;Zhu and Wang, 2000). Although Arabidopsis serves as the model system for most plant processes, it suffers from two major weaknesses in consideration of plant-microbe interactions: the absence of symbiotic associations with mycorrhizal fungi and with rhizobia.…”
mentioning
confidence: 99%